The Retention of the Employees as Long as Possible in the Organization, Through Finding the Right Factors of Motivation. Albania as a Case of Study - Stillo, Sonela; Furxhi, Gentisa (European Journal of Economics and Business Studies, 2016)
One of the main objectives of an organization is the achievement of productivity, performance and high standards through the efficient use of the human resources and the application of the right technologies for combining the work force with the quantity of work. The job of the staff is done perfectly if you put the right person in the right position, in the right time. But to retain is more important than to employ. A talented employee will never run out of possibilities. The retention of employees is a process in which the employees are encouraged to stay in the organization for a maximal period of time. Even though the retention of the employees is a hard job for the organization, it is important for the organization as well as for the employee himself. If we assure the fulfillment of this important objective of the management of the human resources, thus the preservation of the human capacities, than we are in the right path of minimizing the turnover in the organization. For this to be possible it must be paid maximal attention to the employees, making them feel comfortable physically as well as psychologically in the workplace. Such thing requires the readiness of the organization to motivate the human resources. Exactly, the motivation of the employees is one of the most important factors that help the employer to improve the organizational and the employee’s performance. The purpose of this study is evidencing the main factors that impact the level of motivation of the employees, their retention in the organization and a valuation of the rate of this impact.The data gathered from both public and private sector were analyzed through the software SPSS using the analyze of t-test, frequency, the pearson correlation, density.
Keywords: SPSS using the analyze of t-test, frequency, the pearson correlation, density.